The Dayak Tribe's Bonum Commune Crisis: Traditional Farming Versus Modern Economic Activities - Raharso, Alphonsus Tjatur; Isharianto, Rafael; Ardi, Mikael (Litbang STFT Widya Sasana Malang, 2025)
This research highlights the local wisdom of the Dayak people of Kalimantan in clearing agricultural land. The tradition of farming for hundreds of years has built bonum commune and become an index of happiness for the Dayak community. However, local wisdom has been marginalized by a very progressive national development program, thanks to the support of technological advances and market needs. This research confronts the traditional way of Dayak communities with the modern plantation industry in managing forests. The two ways are evaluated ethically-morally, using literature studies in the perspective of ecological ethics. The research found that the Dayak custom of farming, which is full of socio-religious values, is carried out by burning a limited and measurable area of forest. After harvesting, the field area is reforested. In contrast, extensive and aggressive deforestation, without the prospect of reforestation, is carried out by oil palm plantation companies, both government and private. The current development program prioritizes oil palm plantations, and prohibits the Dayak tradition of farming. This is destroying the sociocultural life of the Dayak people that has been lived for hundreds of years. This research proposes that in carrying out macroeconomic activities in Kalimantan, government or private companies still accommodate local wisdom, and carry out locality-based development strategies. Meanwhile, Dayak communities need to adapt by carrying out microeconomic activities in accordance with applicable laws using ecological technology, while maintaining their socio-religious values.